Trade, growth, and inequality - Bliss, Christopher. J. (Oxford ; New York : Oxford University Press, 2007)
Links the two fields of trade theory and economic development. It combines mathematical rigour with an exceptional breadth of approaches, including institutions, history and comparative economics. Uniquely, the book focuses not only on countries participating in globalized trade but also those failing to participate.
Includes bibliographical references (p. 301-312) and index.
oif 17/09/15
Loan
Keywords: International trade; Economic development; Developing countries -- Commerce